2015
DOI: 10.18632/genesandcancer.88
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma cell lines and primary tumors proteome: protein biosynthesis and Immune system as potential therapeutic targets

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…We also identified seven biological pathways from the KEGG database significantly overrepresented ( Figure 3B), in line with the GO biological processes, with emphasis on the following pathways: "protein processing in endoplasmic reticulum" and "ribosome" (both related to protein biosynthesis), and "oxidative phosphorylation", "fatty acid degradation", and "metabolism pathways "(all of them related to energy metabolism). In addition, we also identified an overlap of 24 upregulated DEP proteins from this study, compared to the data from our 2015 study (19), where we evaluated the protein expression of tumor plasma cells versus plasma cells from healthy donors ( Figure 5).…”
Section: Mm-mc Cd138-cd105vs Hd-mc Cd138-cd105-mentioning
confidence: 82%
See 3 more Smart Citations
“…We also identified seven biological pathways from the KEGG database significantly overrepresented ( Figure 3B), in line with the GO biological processes, with emphasis on the following pathways: "protein processing in endoplasmic reticulum" and "ribosome" (both related to protein biosynthesis), and "oxidative phosphorylation", "fatty acid degradation", and "metabolism pathways "(all of them related to energy metabolism). In addition, we also identified an overlap of 24 upregulated DEP proteins from this study, compared to the data from our 2015 study (19), where we evaluated the protein expression of tumor plasma cells versus plasma cells from healthy donors ( Figure 5).…”
Section: Mm-mc Cd138-cd105vs Hd-mc Cd138-cd105-mentioning
confidence: 82%
“…High throughput techniques, such as mass spectrometry, microarray, RNA-seq, among others, allow the generation of an abundant amount of data, allowing to compare patient cells in pathological conditions, such as MM, in relation to cells derived from HD. In 2015, our group published a proteomics study in which we evaluated the protein expression of tumor plasma cells from MM patients in comparison to plasma cells from palatal tonsils from normal individuals ( 19 ). In this study, we identified 81 DEP among these cells (72 upregulated and nine downregulated).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, efforts to define the cell surface proteome of MM have focused on individual cell lines, 16 17 have studied changes in response to one particular therapy, 18 or have used methods that are not optimal for detection of low abundance membrane proteins. 19 As a result, knowledge of clinically informative MM cell surface proteins is lacking. In this study, we first used CSC to define the cell surface N-glycoproteome of four MM cell lines.…”
Section: Introductionmentioning
confidence: 99%